Computer-Based Cognitive Training in Aging - Klimova, Blanka (Frontiers in Aging Neuroscience, 2016)
At present there is a rapid growth of aging population groups worldwide, which brings about serious economic and social problems. Thus, there is considerable effort to prolong the active life of these older people and keep them independent. The purpose of this mini review is to explore available clinical studies implementing computer-based cognitive training programs as intervention tools in the prevention and delay of cognitive decline in aging, with a special focus on their effectiveness. This was done by conducting a literature search in the databases Web of Science, Scopus, MEDLINE and Springer, and consequently by evaluating the findings of the relevant studies. The findings show that computerized cognitive training can lead to the improvement of cognitive functions such as working memory and reasoning skills in particular. However, this training should be performed over a longer time span since a short-term cognitive training mainly has an impact on short-term memory with temporary effects. In addition, the training must be intense to become effective. Furthermore, the results indicate that it is important to pay close attention to the methodological standards in future clinical studies.